(untitled) (Delta Medical College Journal, 2024)
Background: Non-adherence to anti-tuberculosis treatment may result in persistent infectiousness on the part of the patient and a higher rate of treatment failure, relapse and drug resistance and therefore, is a significant barrier to the success in tuberculosis control. Objective: To determine the treatment related factors associated with non-adherence to anti-tuberculosis treatment among tuberculosis patients. Materials and method: This case control study was carried out among purposively selected 47 tuberculosis patients non-adherent to treatment (cases) and 94 tuberculosis patients adherent to treatment (controls) and were interviewed with a semi-structured questionnaire and checklist in selected DOTS centres of Dhaka city. Results: Statistical analysis shows that, factors like delay in seeking tuberculosis treatment for >6 weeks (OR=4.57; 95% CI, 1.48-14.1) and getting medicine weekly once (OR=2.8; 95% CI, 1.13-6.77) were more likely to be associated with non-adherence to treatment. Less frequent visit by health providers (p=0.02), no support for side effect (p=0.042) and non-observation of medication (p=0.009) were also found significant. The reasons behind missing anti-TB doses among non-adherent cases were due to feeling better (53.2%), personal reason (25.5%), feeling worse (19.1%) and forgot to take medicine (2.2%). Conclusion: Mass awareness among the tuberculosis patients is required to improve attitude towards anti-tuberculosis treatment and activities of tuberculosis control programme require further strengthening especially in targeting the patients of low economic status. Delta Med Col J. Jan 2021;9(2): 96-100